2007
DOI: 10.3354/meps06931
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile growth in barnacles: combined effect of delayed metamorphosis and sub-lethal exposure of cyprids to low-salinity stress

Abstract: Delayed metamorphosis can affect post-metamorphic performance in a variety of marine invertebrate species, possibly through effects on larval energy reserves. Nevertheless, the consequences of the 'latent effects' of natural environmental conditions and the proximate causes of the effects have rarely been examined. We documented the combined effect of delayed metamorphosis and sub-lethal exposure of larvae to low-salinity stress on depletion of energy reserves, metamorphic success and juvenile growth rates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
(50 reference statements)
3
24
1
Order By: Relevance
“…Interestingly, our study also revealed that high-temperature and lowsalinity environments are comparable, if not stronger, drivers of negative latent effects (on settlement) than delayed settlement in this species (55% vs. 48% reduction, respectively). Consistent with our observations, cyprid larvae of the barnacle Balanus amphitrite exhibited negative latent effects of low salinity on postmetamorphic growth that were as severe as latent effects caused by delayed metamorphosis (Thiyagarajan et al 2007). …”
Section: Latent Effects Of Harsh Larval Environments Were More Pronousupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, our study also revealed that high-temperature and lowsalinity environments are comparable, if not stronger, drivers of negative latent effects (on settlement) than delayed settlement in this species (55% vs. 48% reduction, respectively). Consistent with our observations, cyprid larvae of the barnacle Balanus amphitrite exhibited negative latent effects of low salinity on postmetamorphic growth that were as severe as latent effects caused by delayed metamorphosis (Thiyagarajan et al 2007). …”
Section: Latent Effects Of Harsh Larval Environments Were More Pronousupporting
confidence: 91%
“…In the barnacle Balanus amphitrite, low-salinity stress during the larval stage reduced post-metamorphic growth rates (Thiyagarajan et al 2007). In contrast, low salinity caused FIG.…”
Section: Latent Effects Of Harsh Larval Environments Were More Pronoumentioning
confidence: 99%
“…Similarly, latent effects resulting from exposing larvae to low salinity have been documented in the polychaete C. teleta (Pechenik et al, 2001) and the barnacle B. amphitrite (Thiyagarajan et al, 2007). Adding the results of our study to these previously documented cases of salinity-induced latent effects lends weight to the necessity of considering the environmental conditions larvae are exposed to when attempting to predict the responses of juvenile or adult populations.…”
Section: Latent Effects Of Larval Exposure To Low Salinitymentioning
confidence: 57%
“…Latent effects have been documented following larval exposure to low food concentration (the gastropod Crepidula fornicata: Pechenik et al, 1996a,b), ocean acidification (the oyster Ostrea lurida: Hettinger et al, 2012), low salinity (the polychaete Capitella teleta: Pechenik et al, 2001; the barnacle Balanus amphitrite: Thiyagarajan et al, 2007), copper (the bryozoan Watersipora subtorquata: Ng and Keough, 2003) and delayed larval metamorphosis (the colonial ascidian Diplosoma listerianum: Marshall et al, 2003;B. amphitrite: Pechenik et al, 1993; the bryozoan Bugula stolonifera: Woollacott et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Salinity reductions during presettlement periods can reduce post-metamorphic growth rates and survival for various marine invertebrates (Pechenik et al, 2001;Thiyagarajan et al, 2008). Vermeij et al (2006) tested salinity stress on Montastraea faveolata larvae and how that infl uenced subsequent post-settlement FIGURE 4.…”
Section: Larval Condition Upon Arrivalmentioning
confidence: 99%